Monitoring Iklim Mikro pada Greenhouse Secara Real Time Menggunakan Internet of Things (IoT) Berbasis Thingspeak - Anri Kurniawan; Andika Ristiono; Slamet Sulistiadi (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2021)
Farm cultivation in the highlands is constrained by the long rainy season, less efficient sunlight and susceptible to pests and diseases. One of the solutions in cayenne pepper cultivation is using hydroponics and greenhouse s to minimize pests and diseases that come from the soil and are carried by the wind. The purpose of this research is to produce "SMART-IGHIOT" a control system based on the Internet of Things using Dutch bucket hydroponics in a portable greenhouse. The technology applied is in the form of monitoring and controlling temperature, humidity, air temperature and light intensity using sensors integrated with the ESP32 microcontroller. The ESP32 is connected to the Thingspeak webserver to display sensor measurement results in real-time. The design of the monitoring system for light intensity, temperature and humidity in the greenhouse can be maximized so that environmental conditions can be optimized. The performance of using greenhouse s can maximize the intensity of sunlight, the highest at 12.00, while the lowest temperature at 03.00 to 05.00 WIB. While the highest temperature is at 13.00 and the highest humidity is at night. Keywords: dutch bucket, greenhouse, IoT, microclimate, Thingspeak